Teachers' Perception of The Effectiveness of PMM (Platform Merdeka Mengajar) in Elementary School 82 Bengkulu City - Cahya Negara, Agung; Sujarwati, Iis; Harahap, Alamsyah (Edu-Ling: Journal of English Education and Linguistics, 2024)
Abstract PMM (Platform Merdeka Mengajar) has played an important role in transforming the educational practices across Indonesia. It has innovative approach and digital platform that have significantly impacted teaching methodologies and student learning experiences, helping in a new era of online and interactive education. The objective of this study was to explore teachers' perceptions of the effectiveness offered by PMM in SD Negeri 82 Kota Bengkulu. This research was descriptive quantitative. The instrument used in this research was questionnaire. The questionnaires were distributed to 35 teachers at SD Negeri 82 Kota Bengkulu. The results showed that most teachers at SD Negeri 82 Kota Bengkulu perceive PMM as aligned with the current curriculum, indicating a positive perception of its relevance to educational standards. The teachers acknowledge significant learning benefits associated with PMM, such as improved student engagement, better comprehension of topics, and enhanced academic performance. While some teachers express satisfaction with the support received from the school and government regarding PMM, others highlight the need for additional resources and training opportunities. However, the aspect of parental involvement received a negative response, highlighting areas for improvement in encouraging collaborative partnerships, parental education, and communication channels. Keywords: Teachers’ Perception; Effectiveness; PMM (Platform Merdeka Mengajar)